1999
DOI: 10.1105/tpc.11.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Structural P Proteins in the Phloem

Abstract: Phloem-specific proteins (P proteins) are particularly useful markers to investigate long-distance trafficking of macromolecules in plants. In this study, genus-specific molecular probes were used in combination with intergeneric grafts to reveal the presence of a pool of translocatable P protein subunits. Immunoblot analyses demonstrated that Cucurbita spp P proteins PP1 and PP2 are translocated from Cucurbita maxima stocks and accumulate in Cucumis sativus scions. Cucurbita maxima or Cucurbita ficifolia PP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(53 citation statements)
references
References 32 publications
2
51
0
Order By: Relevance
“…Kim et al [48] and Achor et al [49] showed that the accumulation of a lectin-like protein, at the sieve plates is associated with blockage of the translocation stream in HLB-affected citrus plants. Additionally, studies have demonstrated that lectin-like proteins interact with RNA molecules and are involved in long-distance trafficking, suggesting a role for these proteins in long-distance signaling response in HLB-affected citrus plants [39, 50]. …”
Section: Resultsmentioning
confidence: 99%
“…Kim et al [48] and Achor et al [49] showed that the accumulation of a lectin-like protein, at the sieve plates is associated with blockage of the translocation stream in HLB-affected citrus plants. Additionally, studies have demonstrated that lectin-like proteins interact with RNA molecules and are involved in long-distance trafficking, suggesting a role for these proteins in long-distance signaling response in HLB-affected citrus plants [39, 50]. …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand host plants might induce the production of lectin-like proteins as a defensive attempt to prevent the spread of Las by sealing off the sieve tubes. Additionally studies have demonstrated that lectin-like proteins are able to interact with RNA molecules, are involved in the long-distance trafficking of macromolecules and may play a role in long-distance signaling in response to infection by plant pathogens [49,50]. …”
Section: Resultsmentioning
confidence: 99%
“…The companion cell/sieve element complexes of the EFP strands are similar in shape and diameter to the FP (Golecki et al, 1999). However, absence of the EFP from minor veins of source leaves suggests that this particular phloem is not involved in sugar loading (Turgeon and Oparka, 2010).…”
Section: Extrafascicular Phloem Vs Fascicular Phloemmentioning
confidence: 99%